Effect of Moringa oleifera Leaf Extracts on Depression in Rheumatoid Arthritis Patients - Afifah Syifaul Ummah; Faizal Muhammad; Yulie Erida Nur Rahmawati; Isa Ridwan; Arief Nurudhin1; Eillien Ramadhani Fauzi; Ratih Tri Kusuma Dewi; Yulyani Werdiningsih (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Depression is a mental disorder that is increasingly common nowadays. It can emerge as morbidity in chronic diseases such as rheumatoid arthritis (RA). The leaf extract of Moringa oleifera (MO) has shown to be a complementary therapy in depression, besides its anti-inflammatory role. This study aimed to evaluate the effect of MO leaf extract on Depression in RA patients. Methods: This quasi-experimental study with a pretest-posttest control group design comprised 32 RA patients. The participants were divided into the control (n = 16) and intervention (n = 16) groups. The intervention group received two MO leaf extract-containing capsules b.i.d. for 28 days. The depression was evaluated by Beck Depression Inventory (BDI-II) and serum cortisol test. Statistical analyses used both paired and unpaired t-tests. Results: The posttest means comparison of BDI-II and serum cortisol showed a significant difference between groups (p = 0.031 and p = 0.015, respectively). The pretest-posttest difference within the control group did not show significant improvement in BDI-II and serum cortisol (p = 0.076 and p = 0.106). Meanwhile, significant BDI-II and serum cortisol improvement were found in the intervention group (p = 0.003 and p = 0.048, respectively). Conclusion: MO leaf extract reduces depression in RA patients based on BDI-II and serum cortisol assessment. REFERENCE 1. Wang J, Wu X, Lai W, Long E, Zhang X, Li W, et al. Prevalence of depression and depressive symptoms among outpatients: a systematic review and meta-analysis. BMJ Open 2017;7. doi: 10.1136/BMJOPEN-2017-017173. 2. Pedersen ME, Szewczyk B, Stachowicz K, Wieronska J, Andersen J, Stafford GI, et al. Effects of South African traditional medicine in animal models for depression. J Ethnopharmacol 2008;119:542–8. doi:10.1016/J.JEP.2008.08.030. 3. Matcham F, Rayner L, Steer S, Hotopf M. The prevalence of depression in rheumatoid arthritis: a systematic review and meta-analysis. Rheumatology (Oxford) 2013;52:2136–48. doi:10.1093/RHEUMATOLOGY/KET169. 4. Tański W, Szalonka A, Tomasiewicz B. Quality of Life and Depression in Rheumatoid Arthritis Patients Treated with Biologics – A Single Centre Experience. Psychol Res Behav Manag 2022;15:491. doi:10.2147/PRBM.S352984. 5. Santarsieri D, Schwartz TL. Antidepressant efficacy and side-effect burden: a quick guide for clinicians. Drugs Context 2015;4. doi:10.7573/DIC.212290. 6. Hritcu L, Ionita R, Postu PA, Gupta GK, Turkez H, Lima TC, et al. Antidepressant Flavonoids and Their Relationship with Oxidative Stress. Oxid Med Cell Longev 2017;2017. doi:10.1155/2017/5762172. 7. Islam Z, Islam SMR, Hossen F, Mahtab-Ul-Islam K, Hasan MR, Karim R. Moringa oleifera is a Prominent Source of Nutrients with Potential Health Benefits. Int J Food Sci 2021;2021. doi:10.1155/2021/6627265. 8. Kou X, Li B, Olayanju JB, Drake JM, Chen N. Nutraceutical or Pharmacological Potential of Moringa oleifera Lam. Nutrients 2018;10. doi:10.3390/NU10030343. 9. Kaur G, Invally M, Sanzagiri R, Buttar HS. Evaluation of the antidepressant activity of Moringa oleifera alone and in combination with fluoxetine. J Ayurveda Integr Med 2015;6:273. doi:10.4103/0975-9476.172384. 10. Gupta K, Attri J, Singh A, Kaur H, Kaur G. Basic concepts for sample size calculation: Critical step for any clinical trials! Saudi J Anaesth 2016;10:328. https://doi.org/10.4103/1658-354X.174918. 11. García-Batista ZE, Guerra-Peña K, Cano-Vindel A, Herrera-Martínez SX, Medrano LA. Validity and reliability of the Beck Depression Inventory (BDI-II) in general and hospital population of Dominican Republic. PLoS One 2018;13. doi: 10.1371/JOURNAL.PONE.0199750. 12. Lindholm H, Ahlberg J, Sinisalo J, Hublin C, Hirvonen A, Partinen M, et al. Morning Cortisol Levels and Perceived Stress in Irregular Shift Workers Compared with Regular Daytime Workers. Sleep Disord 2012;2012:1–5. doi:10.1155/2012/789274. 13. Adedapo AA, Falayi OO, Oyagbemi AA. Evaluation of the analgesic, anti-inflammatory, anti-oxidant, phytochemical and toxicological properties of the methanolic leaf extract of commercially processed Moringa oleifera in some laboratory animals. J Basic Clin Physiol Pharmacol 2015;26:491–9. doi:10.1515/JBCPP-2014-0105. 14. Brunello N, Mendlewicz J, Kasper S, Leonard B, Montgomery S, Nelson JC, et al. The role of noradrenaline and selective noradrenaline reuptake inhibition in depression. Eur Neuropsychopharmacol 2002;12:461–75. doi:10.1016/S0924-977X(02)00057-3. 15. Vallerand IA, Patten SB, Barnabe C. Depression and the risk of rheumatoid arthritis. Curr Opin Rheumatol 2019;31:279. doi:10.1097/BOR.0000000000000597. 16. Vauzour D, Vafeiadou K, Rodriguez-Mateos A, Rendeiro C, Spencer JPE. The neuroprotective potential of flavonoids: a multiplicity of effects. Genes Nutr 2008;3:115–26. doi:10.1007/s12263-008-0091-4. 17. Gutierrez-Merino C, Lopez-Sanchez C, Lagoa R, K. Samhan-Arias A, Bueno C, Garcia-Martinez V. Neuroprotective Actions of Flavonoids. Curr Med Chem 2011;18:1195–212. doi:10.2174/092986711795029735. 18. Reif A, Schmitt A, Fritzen S, Lesch K-P. Neurogenesis and schizophrenia: dividing neurons in a divided mind? Eur Arch Psychiatry Clin Neurosci 2007;257:290–9. doi:10.1007/s00406-007-0733-3. 19. Sreelatha S, Padma PR. Antioxidant Activity and Total Phenolic Content of Moringa oleifera Leaves in Two Stages of Maturity. Plant Foods Hum Nutr 2009;64:303–11. doi:10.1007/s11130-009-0141-0. 20. Xiao X, Wang J, Meng C, Liang W, Wang T, Zhou B, et al. Moringa oleifera Lam and its Therapeutic Effects in Immune Disorders. Front Pharmacol 2020;11. doi: 10.3389/FPHAR.2020.566783/FULL. 21. Saleem A, Saleem M, Akhtar MF, Shahzad M, Jahan S. Moringa rivae leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers. Inflammopharmacology 2020;28:139–51. doi:10.1007/S10787-019-00596-3. 22. Stohs SJ, Hartman MJ. Review of the Safety and Efficacy of Moringa oleifera. Phyther Res 2015;29:796. doi:10.1002/PTR.5325. 23. Park K, Jaekal E, Yoon S, Lee S-H, Choi K-H. Diagnostic Utility and Psychometric Properties of the Beck Depression Inventory-II Among Korean Adults. Front Psychol 2020;10. doi:10.3389/fpsyg.2019.02934. 24. Hemmingsen SD, Jensen NA, Larsen PV, Sjögren JM, Lichtenstein MB, Støving RK. Cortisol, Depression, and Anxiety Levels Before and After Short-Term Intensive Nutritional Stabilization in Patients With Severe Anorexia Nervosa. Front Psychiatry 2022;13. doi:10.3389/fpsyt.2022.939225.